Síntese e avaliação de catalisadores para a produção de hidrogênio a partir das reações de reforma com vapor d?água e reforma oxidativa do etanol - Furtado, Andréia Cristina (2009)
Catalysts were synthesized and selected for the ethanol steam reforming and oxidative reforming reactions. The work was divided into two stages: the first was made to select the best active phase, which was used, in the second stage, in the selection of the best support. The best active phase/support combination should maximize hydrogen production and minimize the occurrence of parallel reactions, which lead to unwanted products. The catalysts were prepared by excess solvent impregnation of precursor salts on the support, followed by drying, pressing, calcination, grounding and sieving, resulting in particles with average diameter between 0.4 mm and 0.8 mm. The catalysts synthesized in the first stage were Me-Cu bimetallic catalysts (Me = Ni, Pt, and Pd) supported in g-Al2O3 and a-Al2O3 phases. In the second stage, the main focus was on the influence of different supports (ZnO, Nb2O5, and CexZr1-xO2) on the catalytic process of the ethanol reforming. The amounts of precursor salts were determined in order to obtain, after calcination, catalysts with nominal mass fractions of metals Ni, Cu, Pt, and Pd equal to 10%, 1%, 2%, and 3%, respectively. The metal precursors used were Ni(NO3)2.6H2O, Cu(NO3)2.3H2O, H2PtCl6.6H2O, and PdCl2. The catalysts were characterized by TPR, XRD, BET surface area, atomic absorption, TPD-NH3, isopropanol decomposition reaction, and DRS in the UV-vis range. The supports were submitted to thermogravimetric analysis and differential scanning calorimetry. The catalysts containing nickel had the metal surface area, metal dispersion, and metal particle size determined by TPD-H2. The catalytic tests of ethanol steam reforming were performed at atmospheric pressure and temperature of 400 oC with 2.5 g of catalyst. The analysis of the first stage results pointed to the Ni-Cu active phase as the most suitable for hydrogen production. Moreover, the production of gas was higher using a feed molar ratio of liquid reagents H2O/C2H5OH equal to 10 and space velocity fixed in 70 dm3/h.gcat (after vaporization). On the second stage, different supports were analyzed with the same active fase, 10% Ni-1% Cu, selected in the first stage. Ni- Cu/Ce0,6Zr0,4O2 was found to be the most active and selective catalyst for hydrogen production from ethanol steam reforming reaction. The other products were minimized by the reduction of unwanted reactions. Moreover, the catalyst was very stable for hydrogen production over the 8 h of reaction. As for the other catalysts, the yield of unwanted products was higher. Hydrogen production occurred preferentially by reactions such as ethanol dehydrogenation to acetaldehyde and ethanol decomposition. The results also showed the strong influence of catalyst acidity on the distribution of products. The presence of ethylene and diethyl ether was attributed to acid sites on the catalytic surface. The activity of the catalysts was also evaluated in the ethanol oxidative reforming, with O2/C2H5OH equal to 0.8. The incorporation of oxygen clearly reduced the efficiency of the Ni-Cu/Ce0,6Zr0,4O2 catalyst. The decrease in performance was marked by a strong catalyst deactivation, a reduction in hydrogen production, and a strong elevation in the amount of products from the oxidation reaction. In general, the addition of oxygen to the reagent mixture caused a reduction in hydrogen production when compared to the ethanol steam reforming, independent of the catalyst.